Finger lickin' fifteen - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2009)
New Jersey bail-bonds office worker Lula is a witness to celebrity chef, Stanley Chipotle, losing his head, literally. Now Lula and Stephanie Plum, a bond enforcement officer, are on the hunt to identify the killers before Lula is next on the chopping block. Meantime, security expert Carlos Manoso, aka Ranger, has recruited Stephanie for a top secret mission. Someone on the inside at Rangeman is leaking client information, determined to bring the company down. Can Stephanie hunt down a killer, a traitor, and keep her Grandma out of the sauce?